Muslim Refugee Girls in Malala Yousafzai’s We Are Displaced - Dahlan Dahlan; Jumharia Djamereng; Sindi klaudiya (Muslim English Literature, 2022)
The research intends to find out the kinds of discrimination faced by the refugee girls and also life experiences of the refugee girls that related to the author’s life. Malala as the writer of the memoir We Are Displaced describes her experiences as a Muslim woman who is often treated unfairly both in the homeland and in the host land. As Malala had seen many discriminations in many places, she was inspired to write all discrimination as the movement against that discrimination. Therefore, feminism is a study of efforts to change gender roles, sexist practices, and sexual norms that often limit personal development. This research uses content analysis, especially close textual analysis. The results of this research show that there are 3 kinds of discrimination of the refugee girls. They are: 1) Racial Discrimination, 2) Gender Discrimination, and 3) Social Class Discrimination. This research also shows that some of the refugee girls have the same life experience as the author based on educational value, they are: 1) Independence value, 2) Creativity value, 3) Social Concern value.